The Scientific Values of Malaysian Herbal Products - Ibrahim Jantan, (penerbit ukm, 2006)
This paper attempts to examine the real values of Malaysian herbal products in the aspects of quality, safety and efficacy as curing agents. In so doing it will also determine the driving force behind the intense public interest for herbal medicine as alternative or complementary to conventional medicine. Most herbal products in the Malaysian market are not sufficiently provided with information on their ingredients, indications, dosage, pharmacology, contraindications and possible side-effects. Most published information on the products on evidence of safety and efficacy is not supported with scientific evidence. The present practice of traditional medicine still depend heavily on information obtained through ethnopharmacological experiences. However, the herbal product market is experiencing a tremendous growth and there is an increased trend of incorporating herbal therapy into modern medical practice by many mainstream health professionals. Unfortunately, the popularity of herbal products is more associated with consumer attitudes and the ability of the herbalist to influence rather than their tru quality as medicinal agents. Many people are exploited due to ignorance on the real value of herbals as therapeutic agents. It is especially disappointing when popular media, promotional literature and talk shows by individuals promoting quackery are given much publicity. Even worse, many individuals trained in the health sciences are promoting quackery. This has often left the consumers with the perception tha the authority condones the improper use of herbal products. Thus, It is important for pharmacists and physicians to be trained in traditional herbal medicine so that they can educate the public on the benefits, quality, safety and proper use of herbal products.